Susu Fermentasi Anti Hipertensi ( SUFERANTIH) - Hamnah Al Atsariyah (Ikatan Senat Mahasiswa Farmasi Seluruh Indonesia, 2020)
Work is a man's duty when he is the head of the household. Long working hours cause physical fatigue both physically and psychologically. It will significantly affect the lifestyle that has an impact on the quality of health. Hypertension is a disease that is triggered due to physical and psychological fatigue. The drug that is often used as a pharmacological therapy for hypertension is captopril, which functions as an angiotensin converting enzyme inhibitor (ACE I). On the other hand captopril has a high toxicological effect including kidney disorders and hypersensitivity reactions appear. So it is necessary to innovate antihypertensive therapy which functions the same as captopril but has no side effects. Fermented milk has a compound that has the potential as an ACE inhibitor which acts to prevent the formation of aldosterone-producing angiotensin II which causes a rise in blood pressure. Fermented milk is a mild preparation that can be consumed without knowing age restrictions. Consumption of fermented milk can be combined with a variety of healthy food menus and other drinks. In the process of lactic acid bacterial fermentation, it will turn beta casein into a compound that has the potential to be ACE I. However, adding to the great potential of fermented milk as an antihypertensive agent, people's misconceptions about milk need to be corrected first. Therefore,